MAIN METHODOLOGICAL PRINCIPLES OF SOLVING ENVIRONMENTAL PROBLEMS IN URBAN PLANNING - Pozdnyakov, Andrey Leonidovich (Journal of Applied Engineering Science, 2017)
Settlement as an aggregate of global, regional and local processes of location of a growing population on the planet on an increasingly large scale determines the development of an urbanized environment on the Earth, the main material element of the life activity of society in its interaction with the biosphere. At the same time, the most important historical task of mankind is the preservation of the biosphere as the main prerequisite for the life on earth of man as a biological species and as a social being. At the same time, the problem of the methodology of security activities and the utmost improvement of the environment in the immediate habitats and the maximum concentration of people – cities, towns and other settlements, whose impact on the natural environment has reached global proportions, and, nevertheless, continuously increases.
Keywords: Urboecology; Urban Development Methodology; Territorial Planning